Nowe instrumenty planowania przestrzennego w zarządzaniu gminą (projekt ustawy o zagospodarowaniu przestrzennym gmin opracowany przez Ministerstwo Infrastruktury) - Feltynowski, Marcin (The New Spatial Development in Governing a Commune (the Bill of Spatial Distribution in Communes Developed by the Department of Infrastructure), 2007)
The article describes the currently functioning act, which deals with the arrangement and development of space, clashing the records of the act currently in force with the department's bill. The project presented in the article anticipates a localization of plans for communes to different degrees of particularization. The aim of the article is to present new studies, the ability to apply them in practice and an initial attempt to evaluate the effectiveness of shaping communal space through new local plans and their influence on governing the commune. The presented local plans are becoming the basis of governing the commune's space via local authorities. The starting points in evaluating the efficacy of the documents above are: the acts presented in the project concerning particular plans and the opinions included in the project abstract broadened by the author's own analyses and ideas.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 655-666